The mirage of protection: Investigating sex victims’ legal consciousness of police engagement in China - Liu, Jingwei (International review of victimology, 2025)
Exploring the legal consciousness of sex victims in China through empirical research is an important area that deserves further investigation. This research is especially relevant in the present context as legislation against sexual harassment is being implemented, and society is increasingly prioritizing the well-being of victims. Through the legal estrangement framework, this article explores the changes in victims’ legal consciousness as a result of their interactions with law enforcement agencies, specifically the police. By employing purposive sampling for selected in-depth interviewees, this study is finally based on 20 in-depth interviews with victims of sexual harassment in China, which found that their attitudes and perspectives underwent a significant shift before and after reporting their experiences to the police. The findings showed that, initially, most of the victims believed that the police would provide them with the expected relief and justice. However, their interactions with the police shattered this belief. This transformation of the victim’s legal consciousness occurs within the interrelated dimensions of the legal estrangement framework: accessibility, legitimacy, trust, and empowerment. This study also highlights how these interactions with the police force shape the victims’ identity and contribute to broader social inequality. Finally, the study offers policy implications.